2022
DOI: 10.3390/toxins14120870
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aflatoxin M1 in Cow, Goat, Buffalo, Camel, and Yak Milk in China in 2016

Abstract: In this present study, 195 cow milk, 100 goat milk, 50 buffalo milk, 50 camel milk, and 50 yak milk samples were collected in China in May and October 2016. The presence of aflatoxin M1 (AFM1) was determined using enzyme-linked immunosorbent assay method. For all cow milk samples, 128 samples (65.7%) contained AFM1 in concentrations ranging from 0.005 to 0.191 µg/L, and 6 samples (3.1%) from Sichuan province in October were contaminated with AFM1 above 0.05 µg/L (EU limit). For all goat milk samples, 76.0% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…While Yassin et al (2016) found that the levels of phosphatidylserine, and phosphatidylcholine ranged between ~10-15 µg/mL and ~20-25 µg/mL, respectively, in dromedary milk exosomes which were steady throughout various lactation stages. Several scientific papers suggested that the beneficial health effects of CM might be attributed to its high contents of phospholipids, such as those reported in CMEXOs (Ali et al, 2017;Zheng et al, 2022). After extensive investigations of milk exosomes, it should be clear that no standard amounts of EXOs have been recorded.…”
Section: Exosomes In Milk Of Different Mammalian Speciesmentioning
confidence: 99%
“…While Yassin et al (2016) found that the levels of phosphatidylserine, and phosphatidylcholine ranged between ~10-15 µg/mL and ~20-25 µg/mL, respectively, in dromedary milk exosomes which were steady throughout various lactation stages. Several scientific papers suggested that the beneficial health effects of CM might be attributed to its high contents of phospholipids, such as those reported in CMEXOs (Ali et al, 2017;Zheng et al, 2022). After extensive investigations of milk exosomes, it should be clear that no standard amounts of EXOs have been recorded.…”
Section: Exosomes In Milk Of Different Mammalian Speciesmentioning
confidence: 99%